Antibacterial Activity of Biosynthesized Selenium Nanoparticles Using Extracts of Calendula officinalis against Potentially Clinical Bacterial Strains - José A Hernández-Díaz; Jorge JO Garza-García; Janet M León-Morales; Adalberto Zamudio-Ojeda; Jenny Arratia-Quijada; Gilberto Velázquez-Juárez; Julio C López-Velázquez; Soledad García-Morales (Molecules, 2021)
The use of selenium nanoparticles (SeNPs) in the biomedical area has been increasing as an alternative to the growing bacterial resistance to antibiotics. In this research, SeNPs were synthesized by green synthesis using ascorbic acid (AsAc) as a reducing agent and methanolic extract of Calendula officinalis L. flowers as a stabilizer. Characterization of SeNPs was performed by UV-vis spectrophotometry, infrared spectrophotometry (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and transmission electron microscopy (TEM) techniques. SeNPs of 40–60 nm and spherical morphologies were obtained. The antibacterial activity of marigold extracts and fractions was evaluated by disk diffusion methodology. The evaluation of SeNPs at different incubation times was performed through the colony-forming unit (CFU) count, in both cases against Serratia marcescens, Enterobacter cloacae, and Alcaligenes faecalis bacteria. Partial antibacterial activity was observed with methanolic extracts of marigold leaves and flowers and total inhibition with SeNPs from 2 h for S. marcescens, 1 h for E. cloacae, and 30 min for A. faecalis. In addition, SeNPs were found to exhibit antioxidant activity. The results indicate that SeNPs present a potentiated effect of both antimicrobial and antioxidant activity compared to the individual use of marigold extracts or sodium selenite (Na2SeO3). Their application emerges as an alternative for the control of clinical pathogens.